New U-series and coupled ESR/U-series dating of Hulu Cave, a key Homo erectus site in China - Qingfeng Shao; Christophe Falguères; Yunping Huang; Salah Abdessadok; Wenbo Bao; Jianing He; Xi Chen; Xianglin Zhou; Xinrui Jin; Guilan Hu; Bassam Ghaleb; Yingfei Zhang; et al. (Quaternary Science Reviews, 2026)

Precision nanoparticles for plant thermotolerance: From molecular mechanisms to scalable agriculture - Muhammad Azeem Ashraf; Muhammad Ateeq; Muhammad Amjad; Qingfeng Dong; Hao Ren; Asad Shehzaib; Wang Xue; Liang Chen; Yin-Gang Hu (Plant Science, 2026)

Compound climate hazards revealed by global modeling of drought, heatwaves, and land degradation - Jinping Liu; Yanqun Ren; Qingfeng Hu; Tie Liu; Xi Chen; Patrick Willems; Philippe De Maeyer (Global and Planetary Change, 2026)

Salt-activated bimetal–phenolic nanoadhesive for broad-spectrum micro- and nanoplastic removal across salinity gradients - Zheng Cai; Qingfeng Yao; Lan Zhao; Yan Cao; Yishuang Li; Xianluo Hu; Jingming Gong (Chemical Engineering Journal, 2026)

Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

Biome-dependent forest GPP responses to compound drought and heat from 2001 to 2023 - Jinping Liu; Yanqun Ren; Qingfeng Hu; Shoukai Chen; Mingzhe Li (Agricultural and Forest Meteorology, 2026)

Combined effects of Chlorella application and reduced nitrogen fertilization on nitrogen use efficiency and crop yield in facility vegetable systems - Guoliang Zhao; Jingyu Sun; Xingcheng Hu; Zhengxi Cai; Chen Li; Qingfeng Chen (Applied Soil Ecology, 2026)

An onboard ultra-rapid orbit determination strategy for LEO satellite utilizing spaceborne GNSS data - Peng Luo; Yezhi Song; Xiaogong Hu; Qingfeng Wu; Jianhua Yang; Kai Li; Chengpan Tang; Changshao Chen (Advances in Space Research, 2026)

Complex conjugate faulting of the 2024–2025 Wushi-Akqi (South Tianshan) earthquake sequence constrained by InSAR observations - Jiuyuan Yang; Huaiyang Zhang; Yangmao Wen; Zhenjie Yao; Qingfeng Hu (Advances in Space Research, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Defect-mediated rigid-flexible coupled architecture for upcycling of spent O3-type sodium-ion cathodes - Qingfeng Liu; Jinhua Shi; Fanbin Hu; Zitong Fei; Yun Shen; Haigang Dong; Qi Meng; Peng Dong; Yingjie Zhang (Chemical Engineering Journal, 2026)

Prediction of in situ seafloor sediment sound speed with machine learning - Mujun Chen; Linqing Zhang; Xinfeng Hu; Xiangmei Meng; Guangming Kan; Siyou Tong; Jingqiang Wang; Guanbao Li; Baohua Liu; Qingfeng Hua; Siqi Wu; Xiaobo Zhang (Journal of Oceanology and Limnology, 2026)

Zinc oxide nano-priming fortifies Triticum aestivum L. against salt stress through physio-morphological, biochemical and transcriptomic responses - Muhammad Ateeq; Muhammad Azeem Ashraf; Qingfeng Dong; Hao Ren; Tauqeer Ahmad Yasir; Linzhou Huang; Liang Chen; Yin-Gang Hu (Plant and Soil, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Multi-trait analysis to identify key factors influencing wheat lodging resistance and validation of an integrative lodging index - Hao Ren; Qingfeng Dong; Siting Li; Dezheng Liu; Xubin Zhang; Xue Wang; Liang Chen; Yin-Gang Hu (European Journal of Agronomy, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Mechanically robust and flame-resistant cellulose nanofiber aerogels for efficient smoke pollutant adsorption - Yingying Li; Wenjie Xia; Caoxiong Zhuang; Hongfei Hu; Mingdi Kang; Huinan Wang; Lingling Zhu; Hanwei Wang; Qingfeng Sun (Carbohydrate Polymers, 2026)

New U-series and coupled ESR/U-series dating of Xujiayao (northern China), the type site for Homo juluensis - Qingfeng Shao; Fagang Wang; Junyi Ge; Jean-Jacques Bahain; Pierre Voinchet; Guilan Hu; Xinrui Jin; Rainer Grün; Christopher J. Bae; Xing Song (Quaternary Science Reviews, 2026)

Hybrid molecules with dual inhibition of acetylcholinesterase and tau hyperphosphorylation: design, inhibitory activity evaluation, apoptosis assessment, and mechanistic exploration - Qingfeng Hu; Kai Xu; Qingnian Ran; Wencheng Zhang; Changsheng Gan; Qunling Fang; Ailing Hui (Chemico-Biological Interactions, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Global comparison of temperature and water stress representations in light use efficiency models for gross primary productivity estimation - Enjun Gong; Jing Zhang; Zhihui Wang; Qingfeng Hu; Hongying Bai; Jun Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Multi-scale soil erosion simulation by using an artificial neural network - Wenli Rao; Hongbo Hu; Qingfeng Zhang; Fanfei Ren; Jiaqi Qu (CATENA, 2025)

Groundwater recharge responses to vadose zone thickness variation and rainfall patterns in arid Mongolian pine plantations - Yanwen Bai; Katsutoshi Seki; Qingfeng Zhang; Yujie Hu; Li Wang (Groundwater for Sustainable Development, 2025)

Deciphering the regulatory network of carbon isotope discrimination in bread wheat through genome-wide association studies and genomic prediction - Qingfeng Dong; Shan Lu; Hao Ren; Dezheng Liu; Shen-ao Gao; Xuefen Cai; Shanshan Zhang; Muhammad Ateeq; Liang Chen; Yin-gang Hu (Theoretical and Applied Genetics, 2025)

Effects of conservation agriculture on carbon dynamics across eroded slopes: A global synthesis - Liangang Xiao; Kebing Zhao; Yudi Wang; Rongqin Zhao; Zhixiang Xie; Qingfeng Hu (Agriculture, Ecosystems & Environment, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Using total Kalman filter to extract time-varying signals in PWV time series - Dantong Zhu; Kefei Zhang; Peng Sun; Suqin Wu; Qingfeng Hu; Peipei He; Weibo Yin; Yafei Wang; Junguo Liu (Advances in Space Research, 2025)

Evaluation of slag and tannery sludge based geopolymer after thermal exposure: Properties, phase transformation and Cr leaching behavior - Jialin Chen; Jingfei Zhou; Shoukai Chen; Haibo Shi; Qingfeng Hu; Yingdong Tang (Journal of Cleaner Production, 2025)

Gels stability by improving the hydrophobic region of casein: Effect of the mogrosides on the structure, microstructure, and antioxidant activities in vitro digestive of the casein acid-induced gel - Yingdi Wang; Kun Sun; Yutong Hu; Yujie Lin; Jiaxuan Li; Qingfeng Ban; Fei Liu (Food Hydrocolloids, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

Root Transcriptome of Wheat Genotypes Under Zinc Sufficient and Deficiency Conditions - Gang Liu; Ming Ma; Zhangjun Wang; Qingfeng Li; Fenglou Liu; Yixuan Sun; Shiping Hu; Caixia Liu (Journal of Plant Growth Regulation, 2025)

Novel microfluidic chips integrated with smart devices for in situ detection of foodborne pathogenic bacteria - Ruibin Hu; Wen Wang; Qingfeng Zheng; Jianhan Lin; Hua Yang (Current Opinion in Food Science, 2025)

Deciphering the regulatory network of lignocellulose biosynthesis in bread wheat through genome-wide association studies - Qingfeng Dong; Hao Ren; Xuefen Cai; Yujie Zhang; Shan Lu; Dezheng Liu; Muhammad Ateeq; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Water and land use in China's food systems: Exploring potential mitigation strategies - Wenjun Shi; Hanlin Liu; Yosef Steinberger; Yuanchao Hu; Yang Yang; Qingfeng Meng; Guanghui Xie (Sustainable Production and Consumption, 2025)

Mining genomic regions associated with stomatal traits and their candidate genes in bread wheat through genome-wide association study (GWAS) - Dezheng Liu; Shan Lu; Renmei Tian; Xubin Zhang; Qingfeng Dong; Hao Ren; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Distribution of oil mist particles and air quality improvement in the working area of the cutting workshop - Yuming Zhang; Yang Yang; Qingfeng Cao; Yi Wang; Jia-Ning Fan; Hu Chen; Xin Wang; Fei Wang; Yu Zhou; Mengfan Quan (Journal of Hazardous Materials, 2024)

Constructing local structure heterogeneity in AgNbO3-based antiferroelectrics: Achieving excellent anti-fatigue and energy storage properties - Shuaibing Gao; Zhihang Xu; Haolin Zeng; Meng Shen; Ye Zhu; Haitao Huang; Yongming Hu; Yunbin He; Qingfeng Zhang (Chemical Engineering Journal, 2024)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Heterogeneous feature learning network for multimodal remote sensing image collaborative classification - Xuchu Yu; Zhixiang Xue; Guopeng Yang; Anzhu Yu; Bing Liu; Qingfeng Hu (International Journal of Remote Sensing, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Applications of agent-based models for green development: a systematic review - Qingfeng Meng; Yu Ji; Zhen Li; Xin Hu; Heap-Yih Chong (Environment, Development and Sustainability, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Metagenomic insights into the diversity of 2,4-dichlorophenol degraders and the cooperation patterns in a bacterial consortium - Shunli Hu; Chuangchuang Xu; Yanghe Xie; Lu Ma; Qingfeng Niu; Guomin Han; Junwei Huang (Science of The Total Environment, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Tuning whey protein isolate/hyaluronic acid emulsion gel structure to enhance quercetin bioaccessibility and in vitro digestive characteristics - Ningzhe Wang; Kaida Zhang; Yurou Chen; Jie Hu; Yunqing Jiang; Xibo Wang; Qingfeng Ban (Food Chemistry, 2023)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Discovery of acylated isoquercitrin derivatives as potent anti-neuroinflammatory agents in vitro and in vivo - Jie Liu; Ailing Hui; Jinghe Wang; Qingfeng Hu; Shengnan Li; Yuanli Chen; Zeyu Wu; Wencheng Zhang (Chemico-Biological Interactions, 2023)

Development and characterization of a casein-hyaluronic acid emulsion gel with high water-holding capacity and excellent rheological properties for 3D printing - Ningzhe Wang; Jie Hu; Kaida Zhang; Ye Zhang; Yunqing Jiang; Xibo Wang; Qingfeng Ban (Food Hydrocolloids, 2023)

Highly enhanced direct catalytic oxidation of cyclohexane to adipic acid with molecular oxygen: Dynamic collaboration between zeolite channel micro-environment and Au clusters - Zhiyang Zhang; Mi Hu; Qingfeng Gui; Jing Gu; Wenlong Xu; Qingbo Xiao; Wei Huang (Chemical Engineering Journal, 2023)

Design, synthesis, antibacterial activity, and mechanism of novel resveratrol derivatives containing an 1,3,4-oxadiazole moiety - Ju Peng; Yong Zhang; Xing Liu; Yue Zou; Hongyi Song; Sheng Wang; Qingfeng Cai; Jixiang Chen; Deyu Hu (Pesticide Biochemistry and Physiology, 2023)

Purification technology of oil mist in industrial buildings: A review - Yang Yang; Hu Chen; Qingfeng Cao; Mengdan Qiao; Yi Wang; Jia-Ning Fan; Chunhui Yang; Bo Pan; Xin Wang; Fei Wang; Wenchao Ju; Yu Zhou (Building and Environment, 2023)

Anti-swellable cellulose hydrogel for underwater sensing - Zhuyue Lan; Yuanyuan Wang; Ke Hu; Shitao Shi; Qingyu Meng; Qingfeng Sun; Xiaoping Shen (Carbohydrate Polymers, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Hemipilia yajiangensis (Orchidoideae, Orchidaceae), a new species from western Sichuan, China, based on molecular and morphological evidence - Jiaxin Yang; Shuai Peng; Junjie Wang; Yan Wang; Shixiong Ding; Jing Tian; Guangwan Hu; Qingfeng Wang (Kew Bulletin, 2022)

Recognizing Multivariate Geochemical Anomalies Related to Mineralization by Using Deep Unsupervised Graph Learning - Qingfeng Guan; Shuliang Ren; Lirong Chen; Yao Yao; Ying Hu; Ruifan Wang; Bin Feng; Landing Gu; Wenhui Chen (Natural Resources Research, 2022)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

An Overview of Underwater Vision Enhancement: From Traditional Methods to Recent Deep Learning - Kai Hu; Chenghang Weng; Yanwen Zhang; Junlan Jin; Qingfeng Xia (Journal of Marine Science and Engineering, 2022)
Underwater video images, as the primary carriers of underwater information, play a vital role in human exploration and development of the ocean. Due to the optical characteristics of water bodies, underwater video images generally have problems such as color bias and unclear image quality, and image quality degradation is severe. Degenerated images have adverse effects on the visual tasks of underwater vehicles, such as recognition and detection. Therefore, it is vital to obtain high-quality underwater video images. Firstly, this paper analyzes the imaging principle of underwater images and the reasons for their decline in quality and briefly classifies various existing methods. Secondly, it focuses on the current popular deep learning technology in underwater image enhancement, and the underwater video enhancement technologies are also mentioned. It also introduces some standard underwater data sets, common video image evaluation indexes and underwater image specific indexes. Finally, this paper discusses possible future developments in this area.

A Control Algorithm for Sea–Air Cooperative Observation Tasks Based on a Data-Driven Algorithm - Kai Hu; Xu Chen; Qingfeng Xia; Junlan Jin; Liguo Weng (Journal of Marine Science and Engineering, 2021)
There is tremendous demand for marine environmental observation, which requires the development of a multi-agent cooperative observation algorithm to guide Unmanned Surface Vehicles (USVs) and Unmanned Aerial Vehicles (UAVs) to observe isotherm data of the mesoscale vortex. The task include two steps: firstly, USVs search out the isotherm, navigate independently along the isotherm, and collect marine data; secondly, a UAV takes off, and in its one round trip, the UAV and USVs jointly perform the task of the UAV reading the observation data from USVs. In this paper, aiming at the first problem of the USV following the isotherm in an unknown environment, a data-driven Deep Deterministic Policy Gradient (DDPG) control algorithm is designed that allows USVs to navigate independently along isotherms in unknown environments. In addition, a hybrid cooperative control algorithm based on a multi-agent DDPG is adopted to solve the second problem, which enables USVs and a UAV to complete data reading tasks with the shortest flight distance of the UAV. The experimental simulation results show that the trained system can complete this tas, with good stability and accuracy.

Prevalence of HPV infections in surgical smoke exposed gynecologists - Xiaoli Hu; Qingfeng Zhou; Jian Yu; Jing Wang; Quanmei Tu; Xueqiong Zhu (International Archives of Occupational and Environmental Health, 2021)
Objectives Human papillomavirus (HPV) has been reported recently in surgical smoke generated by gynecological operations. The objective of this study was to investigate whether gynecologists who have performed electrosurgery including loop electrosurgical excision procedure (LEEP), are at risk of acquiring HPV DNA through surgical smoke. Methods A related questionnaire was designed and 700 gynecologist nasal swab samples were collected in 67 hospitals. In addition, the flow fluorescence hybridization technique was used to detect HPV DNA, and the Chi-square test was applied to analyze whether related risk factors including electrical surgery, were correlated with HPV infection in surgeons’ nasal epithelial cells. Results The HPV infection rate in the nasal epithelial cells of the participants who performed electrosurgery (8.96%, 42/469) or LEEP (10.11%, 36/356) was significantly higher than that in the remaining participants who did not perform electrosurgery (1.73%, 4/231) or LEEP (2.91%, 10/344), respectively. The most prevalent HPV genotype in the electrosurgery group was HPV16 (76.19%, 32/42). The HPV-positive rate was increased in the group that had a longer duration of electrosurgery ( P = 0.016). Additionally, the HPV detection rate was significantly lower in electrosurgery operators who used surgical mask (7.64%, 33/432) than in those who did not use protective masks (24.32%, 9/37). Furthermore, the N95 mask (0%, 0/196) significantly reduced the risk for HPV infection compared to that with the general mask (13.98%, 33/236, P < 0.001). Furthermore, 46 participants infected with HPV were followed-up for 3–24 months, and approximately 43.48% (20/46) and 100% (41/41) became negative for HPV DNA, respectively. Conclusions Gynecologists who performed electrosurgery including LEEP were at risk of acquiring HPV infection. Surgical masks, especially the N95 mask, significantly decreased the hazard of HPV transmission from surgical smoke.

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Erratum to: Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Study of infectious conjunctivitis among children in rural areas of Qinghai province - Qingfeng Liang; Xinxin Lu; Mei Wang; Lei Tian; Antoine Labbé; Ailian Hu (Science China Life Sciences, 2016)

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Comparison of the Therapeutic Effectiveness of Sustained Low-Efficiency Dialysis (SLED) with Continuous Blood Purification (CBP) in Critically Ill Patients - Junzhang Cheng; Shouliang Hu; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2013)

Diversity of Gene Cassette Promoter Variants of Class 1 Integrons in Uropathogenic Escherichia coli - Quhao Wei; Xiaofei Jiang; Min Li; Gang Li; Qingfeng Hu; Huoxiang Lu; Guoqiang Chen; Yonglie Zhou; Yuan Lu (Current Microbiology, 2013)

Daidzein Induced Apoptosis via Down-Regulation of Bcl-2/Bax and Triggering of the Mitochondrial Pathway in BGC-823 Cells - Shuyao Tang; Jing Hu; Qingfeng Meng; Xuesong Dong; Kaifu Wang; Yuebin Qi; Chao Chu; Xiaochuan Zhang; Limin Hou (Cell Biochemistry and Biophysics, 2013)

Acute effects of warm footbath on arterial stiffness in healthy young and older women - Qingfeng Hu; Weili Zhu; Yili Zhu; Lu Zheng; Richard L. Hughson (European Journal of Applied Physiology, 2012)